ESTIMATING DEMAND AND SUPPLY FOR COTTON-TEXTILE CLUSTER PRODUCTS - Nasimov , Bakhtiyor (GREEN ECONOMY AND DEVELOPMENT, 2025)
This article examines methods for forecasting demand and supply of products in cotton-textile clusters in Uzbekistan. The study explores the use of predictive models based on cluster production processes, cotton yield, production volume, and export indicators. Furthermore, the development prospects of cotton-textile clusters by 2030 are assessed using both innovative and inertia development scenarios. The results provide practical recommendations for production planning, raw material supply, and improving operational efficiency.